Les Enjeux De La Paix Dans L’eucharistie (Hekima Review, 2005)
In this article the author tries to find out what can be the contribution of the Eucharist in the peace building process. Contrary to the Pax Romana, which wanted peace through weapons, Jesus chose, by his death, to reconcile humanity through non-violence. This is the message at the heart of the Mass and the ‘do this in memory of me’ reminds us our duty to do likewise.